If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6n + -7 = 3n + 2 Reorder the terms: -7 + 6n = 3n + 2 Reorder the terms: -7 + 6n = 2 + 3n Solving -7 + 6n = 2 + 3n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-3n' to each side of the equation. -7 + 6n + -3n = 2 + 3n + -3n Combine like terms: 6n + -3n = 3n -7 + 3n = 2 + 3n + -3n Combine like terms: 3n + -3n = 0 -7 + 3n = 2 + 0 -7 + 3n = 2 Add '7' to each side of the equation. -7 + 7 + 3n = 2 + 7 Combine like terms: -7 + 7 = 0 0 + 3n = 2 + 7 3n = 2 + 7 Combine like terms: 2 + 7 = 9 3n = 9 Divide each side by '3'. n = 3 Simplifying n = 3
| 5x-18=22 | | 3x+7x=8 | | 3n+6=n+10 | | 7x^2-6x-111=0 | | 4.4x+3.8=13.2 | | 4x+34=12x-38 | | 4*0.5-3y=11 | | 2x+9=51-8x | | 10x-29=71 | | 76-4x=7+21 | | 4x-3*-3=7 | | 3x+13=39-5x | | 17x-17+31+9x-69-18x=-39 | | 4x+-3=-1 | | 5+2y=19 | | 9x+3-3x+1=0 | | 2[(4x-2)(4x-2)]=120 | | 6d+4=4d+12 | | x^2+2x^2=400 | | 5z+20-2z=38 | | 4x^2-7x-2= | | 162-5x=5x+22 | | 5(z+4)-2z=38 | | -16x^2=32 | | 88-2=10x+16 | | 9-y=y+5 | | 2x^2+5x+4=x+4 | | 2(y-2)=6 | | 4b+4=7b-5 | | 8(x-7)=x(x-7) | | (10x-4)(3x+2)=0 | | 3a+1=5a-3 |